Revising a Foreign Language Curriculum: A Challenging and Enhancing Experience at a Public School in Bogotá Revisión del currículo de lengua extranjera: Un reto y una experiencia motivante en un colegio público en Bogotá - Marisol Sarmiento S; Maria Nelly Martín D; Martha Camelo G; Aurora Ortiz C; Maritza Ruiz M (Universidad Nacional de Colombia, 2006)
Curriculum design essentially improves education standards; however, for teachers it remains a taboo kept for academics. Nevertheless, curriculum design begins with teacher's reflections. It goes from examining situations to piloting and adjusting proposals. This project involved teachers interested in improving the English learning process at a technical public school. The objective was designing a curriculum that conveyed community interests. First, documents describing existing curricular guidelines were analyzed, then surveys were applied, they evidenced strengths and weaknesses of the current program. Data interpretation showed mixed perceptions regarding the English programme among community members. Even teachers had different perceptions about curricular elements presented in school documents. This phenomenon leads us to consider the implications of a project regarding curriculum design. El diseño curricular es esencial para el mejoramiento educativo, pero los docentes lo creen exclusivo de académicos. Éste parte de la reflexión docente, implica entre otras cosas el diagnóstico de una situación y la implementación de una propuesta. El proyecto fue realizado por docentes interesados en mejorar los procesos de aprendizaje del inglés en un colegio técnico. Se pretendió diseñar un currículo acorde con los intereses de la comunidad. Inicialmente se analizaron los documentos escolares existentes, se aplicaron encuestas que evidenciaron fortalezas y debilidades del programa. La interpretación de datos mostró las diferentes percepciones de la comunidad respecto al programa de inglés; incluso los profesores concebían de manera diferente los elementos curriculares. Esto impulsó la reflexión sobre el diseño curricular.